PENGARUH EFEKTIFITAS FUNGSI AUDIT INTERNAL TERHADAP KINERJA PERUSAHAAN BUMN DIMODERASI OLEH PENGARUH POLITIK ( Studi Empiris di Indonesia ) - Bimantara, Theobaldus M; Laksito, Herry (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2015)
This research aims to examine the relationship between internal audit practice and financial performance of BUMN with consideration to contextual effect of political condition as mediating variable between internal audit practice and financial performance of BUMN In Indonesia. The research model analyzed by using Moderated Regression Analysis (MRA). The results showed that no significant correlation in the effectiveness of the internal audit function on the financial performance BUMN in Indonesia. And then, there is no moderating effect of political context on the effectiveness of the internal audit function influence on the financial performance BUMN in Indonesia. However, the findings of this study used data that might be too little consequence the number of BUMN that is not enough. No evidence of the moderating effects in this study define that political context is not a moderating variable.